2019
DOI: 10.4081/or.2019.7793
|View full text |Cite
|
Sign up to set email alerts
|

Computed-tomography-guided biopsy in suspected spondylodiscitis: Single-center experience including 201 biopsy procedures

Abstract: Our propose is to evaluate CT-guided biopsies in suspected spondylodiscitis with respect to puncture site, microbiology findings, histopathology findings and impact on antibiotic therapy. 86 CT-guided spine interventions in suspected spondylodiscitis comprising 201 biopsy procedures were analyzed. Medical records of all patients were screened for microbiology and histopathology reports as well as date, duration and kind of antibiotic therapy. Statistical analyses included calculation of Chi2-tests and logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
1
10
0
1
Order By: Relevance
“…4 In another more recent meta-analysis that included 10 studies, the positive culture yield of CT-guided biopsy in suspected spinal infection was 33%. 9 The latter percentage of 33% corroborates both the results of some more recent original studies investigating the microbiological yield of the first biopsy in suspected spondylodiscitis 10,11 and a meta-analysis that included 8 studies on the culture yield of repeat biopsy after an initial biopsy with negative findings. 12 This percentage is also considerably lower than the 30%-74% range that was described in the Infectious Diseases Society of America guidelines.…”
Section: Arguments For Routinely Performing Percutaneous Image-guided Biopsysupporting
confidence: 76%
See 2 more Smart Citations
“…4 In another more recent meta-analysis that included 10 studies, the positive culture yield of CT-guided biopsy in suspected spinal infection was 33%. 9 The latter percentage of 33% corroborates both the results of some more recent original studies investigating the microbiological yield of the first biopsy in suspected spondylodiscitis 10,11 and a meta-analysis that included 8 studies on the culture yield of repeat biopsy after an initial biopsy with negative findings. 12 This percentage is also considerably lower than the 30%-74% range that was described in the Infectious Diseases Society of America guidelines.…”
Section: Arguments For Routinely Performing Percutaneous Image-guided Biopsysupporting
confidence: 76%
“…was not significantly different between positive and negative findings on biopsy cultures in patients with suspected spondylodiscitis Özmen et al, 2019 11 CT-guided biopsy was culture-positive in 33.8% with suspected spondylodiscitis Kasalak et al, 2018 12 Systematic review of 8 studies that reported that repeat percutaneous image-guided biopsy (after an initial biopsy with negative findings on cultures) had a positive culture yield ranging between 0% and 60.0% in patients with suspected spondylodiscitis, based on poor-quality evidence Bae et al, 2018 13 The species of blood and biopsy isolates in patients with pyogenic spondylodiscitis were identical in 95.7% Excluding 4 anaerobic isolates, antibiotic susceptibility patterns were identical between blood and biopsy isolates in 97.7% Kim et al, 2014 16 There were no significant differences in treatment success (defined as survival and absence of signs of infection at the end of the therapy) between 75 patients with microbiologically confirmed pyogenic spondylodiscitis (whether by means of blood or biopsy cultures) and 76 patients with clinically diagnosed pyogenic spondylodiscitis without microbiologic confirmation findings that may suggest tuberculous spondylodiscitis (including relative sparing of the intervertebral disc early in the stage of infection, involvement of anterior vertebral body corner, subligamentous spread, multiple vertebral body involvement, extensive paraspinal abscess formation, abscess calcification, and vertebral destruction 15 ) should be exempt from this strategy. 10 Third, the final aim of a percutaneous image-guided biopsy is to improve patient outcome in terms of quality-adjusted life years gained.…”
Section: Key Findings Of Main Studies Discussed In This Articlementioning
confidence: 90%
See 1 more Smart Citation
“…Dies könnte darauf hinweisen, dass bei Vorliegen eines Abszesses der Keimnachweis aufgrund der höheren Keimzahl wahrscheinlicher ist. Özmen et al [18] zeigten jedoch in einer aktuellen Studie, dass die Art und Weise der Biopsie von paravertebralem Gewebe oder Bandscheibengewebe keinen Einfluss auf das Ergebnis der histopathologischen und mikrobiologischen Ergebnisse hat. Andererseits könnte ein Abszessnachweis mit einem fulminanteren Verlauf der Entzündung einhergehen und somit den Verlauf negativ beeinflussen.…”
Section: Diskussionunclassified
“…However, spondylodiscitis is difficult to treat because the positive rate of the causative organisms in spine is low. It is reported that 10–60% positive rate were obtained by fine-needle aspiration [ 5 7 ]. Ineffective conservative treatment may further worsen symptom and lead to serious complications, including epidural abscess, spinal kyphosis deformity, compression of nerves or neurological deficit symptoms [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%